Competitive smart cities through healthy decision-making - Gudes, Ori; Edwards, S.; Yigitcanlar, T.; Pathak, V. (2015)
This chapter examines the challenges and opportunities associated with planning for competitive, smart and healthy cities. The chapter is based on the assumptions that a healthy city is an important prerequisite for a competitive city and a fundamental outcome of smart cities. One of the major decision support systems to support healthy cities is e-health. This chapter focuses on the role of e-health planning, by utilising web-based geographic decision support systems. The chapter proposes the implementation of a novel decision system which would provide a powerful and effective platform for stakeholders to support access online information. This would also provide for better decision-making as well as empower community participation. The chapter highlights the need for a comprehensive conceptual framework to guide the decision process of planning for cities in association with opportunities and limitations. This chapter provides critical insights into using information science-based frameworks.